Probing molecular forces in multi-component physiological membranes. Issue 4 (27th November 2017) - Ray, Arjun; Gräter, Frauke; Thukral, Lipi
Abstract : By combining MD simulations and the newly developed Lipid-Force Distribution Analysis (L-FDA), we explore force transmission in complex multi-component membrane models mimicking eukaryotic organelles. We found that the chemical-moiety based segmentation at membrane interfaces revealed a distinctive distribution of bonded and non-bonded forces in diverse membrane environment. Abstract : Biological membranes are remarkably heterogeneous, composed of diverse lipid mixtures with distinct chemical structure and composition. By combining molecular dynamics simulations and the newly developed Lipid-Force Distribution Analysis (L-FDA), we explore force transmission in complex multi-component membrane models mimicking eukaryotic organelles. We found that the chemical-moiety based segmentation at membrane interfaces revealed a distinctive distribution of bonded and non-bonded forces in diverse membrane environment. Our molecular stress analysis could have far-reaching implications in describing the relationship between membrane mechanical properties and functional states of chemically distinct lipids.